Analisis Kondisi Sosial Ekonomi Masyarakat Nelayan Desa Cabang Kecamatan Bandar Surabaya - Novita Dewi Lestari; Anita Lisdiana (Tapis: Jurnal Penelitian Ilmiah, 2023)
The fishermen community is a society that lives in the area around the coast which depends on fishery products for their life. The fishermen community consists of businessmen and labors. In obtaining an uncertain income, they are also faced with unstable market price conditions due to the Covid-19 pandemic making the socio-economic conditions of fishermen even more difficult. This study aims to analyze the socio-economic conditions of the fishermen community in Cabang Village, Bandar Surabaya District, Central Lampung. The type of research used is qualitative with primary and secondary data sources. Data collection techniques used in this research are observation, interviews and documentation and are supported by literature studies. The results of the study show that there are problems related to work and fishermen's income and education. There is a shift in the profession from fishermen to motorcycle taxi, construction workers and others, to make ends meet. This is due to the non-fulfillment of the economic needs of fishermen families. Apart from that, there have been no significant changes in the education sector, but only followed local government regulations regarding technical online learning. The good news, as time went on and the Covid-19 pandemic passed, the socio-economic conditions of fishermen began to improve and rise from adversity. These conditions looked better and returned to normal when compared to during the Covid-19 pandemic.